2013
DOI: 10.1080/02626667.2012.753147
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic analysis of hydrological drought characteristics using meteorological drought

Abstract: Droughts are an inevitable consequence of climate variability and are pervasive across many regions. Their effects can vary on an extensive scale, depending on the type of drought and people's vulnerability. Crucial characteristics of both hydrological (groundwater, streamflow) and meteorological (precipitation) droughts are related to their durations and severities, and these characteristics are typically correlated. While many studies have addressed the dependencies between these characteristics for either t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(58 citation statements)
references
References 45 publications
1
55
0
2
Order By: Relevance
“…Quantification of this relationship between meteorological and hydrological drought is barely investigated and has proven to be very difficult. To our knowledge, the best effort is elaborated in the recent paper of Wong et al (2012). They found that copulas have more potential to link a hydrological drought to preceding meteorological drought(s) than classical linear correlation techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Quantification of this relationship between meteorological and hydrological drought is barely investigated and has proven to be very difficult. To our knowledge, the best effort is elaborated in the recent paper of Wong et al (2012). They found that copulas have more potential to link a hydrological drought to preceding meteorological drought(s) than classical linear correlation techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Song and Singh (2009) used elliptical copulas to model the joint distribution of drought severity and interval time. Wong et al (2013) applied copulas to investigate the cross-dependence between meteorological and hydrological drought. Xu et al (2015) used copulas to develop a regional drought frequency model by considering drought duration, severity and the affected areas.…”
mentioning
confidence: 99%
“…Drought events became fewer and longer when drought propagated from 3-month SPI to PHDI. These drought properties have been also shown in various studies (Tallaksen et al 2009;Van Loon and Van Lanen 2012;Wong et al 2013;Barker et al 2016). …”
Section: Comparison Between Meteorological and Hydrological Droughtmentioning
confidence: 73%
“…Since atmosphere, surface and subsurface water storages are closely interconnected within the hydrologic cycle, meteorological, agricultural, and hydrological droughts are related with each other. Some studies have tried to find correlations and/or causal relationships between different drought types (Zhai et al 2010;Joetzjer et al 2013;Wong et al 2013;Haslinger et al 2014;Thomas et al 2015;Zhu et al 2016), and have concluded that there is a significant link between different drought types. For example, Haslinger et al (2014) estimated the correlation of four meteorological drought indices [SPI, Standardized Precipitation Evapotranspiration Index (SPEI), Z-index and self-calibrating Palmer Drought Severity Index (scPDSI)] with streamflow.…”
Section: Introductionmentioning
confidence: 99%